Physical Activity Level and Risk of Death: The Severance Cohort Study - Mok, Yejin (Japan Epidemiological Association, 2012)
BACKGROUND: Physical activity decreases deaths from cardiovascular disease and other causes; however, it is unclear whether physical activity is associated with cancer incidence and death in Asian populations. METHODS: Data from 59 636 Koreans aged 30 to 93 years were collected using a questionnaire and medical examination at the Severance Hospital Health Promotion Center between 1994 and 2004. Study participants were followed for a mean duration of 10.3 years. RESULTS: In the exercising group, the multivariate Cox proportional hazards model showed a lower risk of cancer death (hazard ratio [HR] = 0.72, 95% CI = 0.62–0.85) in men but not in women. Those who exercised, as compared with those who did not, had lower risks of all-cause death (men: HR = 0.68, 95% CI = 0.60–0.76; women: HR = 0.65, 95% CI = 0.53–0.79) and noncancer death (men: 0.63, 0.53–0.75; women: 0.52, 0.39–0.69). Physical activity was inversely associated with risk of noncancer death among men and women. CONCLUSIONS: Physical activity was associated with lower risks of cancer death and noncancer death.